THE IMPACT OF THE COMPUTERIZED ACCOUNTING SYSTEM ON THE PERFORMANCE OF INTERNAL AUDITING AND FINANCIAL REPORTS (A STUDY ON A SAMPLE OF COMMERCIAL BANKS LISTED ON THE IRAQ STOCK EXCHANGE) - Fraq Abdulaal Mhalhal; Hazem Ali Muttair; Nawar Ali Makttoof (American Journals, 2022)
The research aims to identify the efficiency and effectiveness of internal auditing and financial reports in light of the use of the computerized accounting system through studying, analyzing and examining the lists and financial reports prepared under a computerized accounting system that is not paper-based by the professionally recognized rules, principles and accounting principles in order to ensure the validity of the results of the activity prepared under To the accounting standards approved by the accountant and to ensure the validity of the results according to the tax return submitted by the taxpayers, the research has reached several conclusions. First, accurately calculating the amount of tax due to taxpayers, and the most critical recommendations were the need to highlight the importance of using computerized accounting systems to raise the efficiency and effectiveness of internal auditing and financial reports by activating them in the banking sector that practices the profession of internal auditing and financial reports.
Keywords: internal audit, internal audit efficiency, financial reports, computerized accounting system